BthTX-II from Bothrops jararacussu venom has variants with different oligomeric assemblies: An example of snake venom phospholipases A2 versatility - Borges, Rafael J. [UNESP]; Salvador, Guilherme H.M. [UNESP]; Campanelli, Henrique B. [UNESP]; Pimenta, Daniel C.; de Oliveira Neto, Mario [UNESP]; Usón, Isabel; Fontes, Marcos R.M. [UNESP] (Elsevier, 2021)
Phospholipases A2 (PLA2s) are found in almost every venomous snake family. In snakebites, some PLA2s can quickly cause local myonecrosis, which may lead to permanent sequelae if antivenom is administered belatedly. They hydrolyse phospholipids in membranes through a catalytic calcium ions-dependent mechanism. BthTX-II is a basic PLA2 and the second major component in the venom of Bothrops jararacussu. Herein, using the software SEQUENCE SLIDER, which integrates crystallographic, mass spectrometry and genetic data, we characterized the primary, tertiary and quaternary structure of two BthTX-II variants (called a and b), which diverge in 7 residues. Crystallographic structure BthTX-IIa is in a Tense-state with its distorted calcium binding loop buried in the dimer interface, contrarily, the novel BthTX-IIb structure is a monomer in a Relax-state with a fatty acid in the hydrophobic channel. Structural data in solution reveals that both variants are monomeric in neutral physiological conditions and mostly dimeric in an acidic environment, being catalytic active in both situations. Therefore, we propose two myotoxic mechanisms for BthTX-II, a catalytic one associated with the monomeric assembly, whereas the other has a calcium independent activity related to its C-terminal region, adopting a dimeric conformation similar to PLA2-like proteins.
Keywords: Basic phospholipase A2; Bothrops jararacussu; BthTX-II; Oligomeric assembly; SEQUENCE SLIDER; Snake venom toxins